Ultrasonic Beam Models for Angle Beam Surface Wave Transducers. Issue 3 (2nd July 2016) - Zhao, Xinyu; Schmerr, Lester W.; Sedov, Alexander; Li, Xiongbing
ABSTRACT: Explicit three-dimensional (3D) point source and multi-Gaussian beam models are obtained for the Rayleigh waves generated by a surface wave angle beam transducer using an angular plane wave spectrum approach. Simulations show that the multi-Gaussian surface wave beam model agrees well with the point source model while being computationally more efficient. The theoretical predictions obtained with the models are also compared to the experimental measurement results where good agreement with the models is found for both on-axis and off-axis field comparisons.